SCALABLE AI SEARCH FOR E-COMMERCE: HYBRID RAG ARCHITECTURE AND VECTOR DATABASES - Цимбал, Артем (SWorldJournal, 2025)
The rapid expansion of multi-tenant e-commerce ecosystems with millions of SKUs demands a new generation of scalable, latency-aware, and cost-efficient AI search architectures. Maintaining stable interactive performance (p95/p99 latency) under fluctuating